IMPACT OF STORAGE TEMPERATURE ON THE SHELF LIFE AND SENSORY QUALITY OF SET YOGURT WITH BIOPROTECTIVE CULTURE - BILJANA TRAJKOVSKA; LJUBICA TRAJKOSKA; GJORE NAKOV; ZLATIN ZLATEV (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Bioprotective cultures like Lactobacillus rhamnosus naturally inhibit spoilage fungi through nutrient competition and antifungal metabolite production, offering a clean-label alternative to synthetic preservatives. This study investigated the impact of bioprotective cultures on set yogurt quality under storage temperatures of 5, 10, and 25 ºC. Physicochemical and sensory parameters were monitored over storage. The pH decreased gradually across all temperatures. Titratable acidity (°SH) increased over time, with higher values observed at elevated temperatures. Sensory analysis revealed higher overall acceptance (SE = 8) at lower temperatures during early storage. Statistical models demonstrated that temperature influenced more than 70 % of the variations in pH, ºSH, and sensory acceptance, with coefficients of determination (R²) ranging from 0.72 to 0.85. Yogurt with FQ9 stored at 10 ºC exhibited an extended shelf life of up to 40 days. This study highlights the effectiveness of bioprotective cultures in improving yogurt shelf life and quality while meeting clean-label demands, offering sustainable solutions for the dairy industry.